Facile preparation of amorphous CenMnOx catalysts and their good catalytic performance for soot combustion. (1st January 2022) - Yu, Di; Peng, Chao; Yu, Xuehua; Wang, Lanyi; Li, Kaixiang; Zhao, Zhen; Li, Zhenguo
Graphical abstract: Highlights: A series of Ce-doped MnOx catalysts were prepared by one-step hydrothermal method. The Cen MnOx catalysts are amorphous phase and different with reported literature. Catalysts exhibit good stability, sulfur and water resistance for soot combustion. Abstract: Diesel engines are widely used because of their low fuel consumption, high fuel efficiency, high reliability, and safety. However, the soot particles contained in diesel engine exhaust have become one of the main sources of urban haze, and their elimination has great significance for environmental protection and economics. In the present study, a series of Cen MnOx catalysts with different Ce contents and calcination temperatures were successfully synthetized via a simple hydrothermal process, and the physicochemical characteristics of the as-prepared catalysts were investigated. That Cen MnOx composite oxides were amorphous, contradicting previous reports that manganese and cerium usually form Mnx Ce1-x Oδ with crystalline structures. Due to Ce doping, the amorphous Ce1 MnOx catalysts have higher specific surface area, greater porosity, and better ability to activate oxygen species than pure MnOx catalysts. The amorphous catalysts also exhibit good stability, sulfur and water resistance for catalytic combustion of soot particles. Among the prepared catalysts, Ce1 MnOx calcinated at 450 °C has the best catalytic activity, the values of T10, T50 and T90 were 258 °C, 327 °C and 370 °C, respectively. Based on their simple preparation, low cost, and good catalytic performance, the amorphous Cen MnOx catalysts show promise for application in soot combustion.